PENERAPAN ANALISIS IMPUT-OUTPUT HIBRID UNTTUK MENGUKUR PENGARUH AKTIVITAS SEKTOR-SEKTOR PEREKONOMIAN TERHADAP KUALITAS LINGKUNGAN KERJA - Faried Wijaya Mansoer (UGM, 1999)
Concern about the negative impact on environment promotes more attention and policy to be directed toward efforts to omplementation of sustainable development, in wich the process hould be optimal and efficeient Various efforts have been tried to measure the environmental impact of economic sectors activities to pursue such objective. This paper presents the application of I-O (Input-Output) hibrid analysis by using Indonesia I-O Table. The result is a quatified impacts by sectoral, kind of energy/waste. and factor of origin namely domestic and import. It might be used as a base analysis for economic, energy-environment, and development policies.